Successful Treatment of Stomal Variceal Bleeding with Percutaneous Injection Sclerotherapy - Takahiro Sato; Mutsuumi Kimura; Masakatsu Yamaguchi; Takumi Ohmura (Archives of Clinical Gastroenterology - Peertechz Publications, 2015)
Bleeding from ectopic varices is often massive and fatal with portal hypertension, and stomal varices can occur in patients with stoma. We aimed to treat a hepatitis B surface antigen positive 69 year-old male with liver cirrhosis associated hepatocellular carcinoma with bleeding stomal varices using percutaneous injection sclerotherapy. Percutaneous injection sclerotherapy was performed under fluoroscopy using 5% ethanolamine oleate with iopamidol (EOI) with a 25 gauge disposable injection needle; 5ml of 5% EOI were injected gradually. Injection sclerotherapy controlled acute bleeding in this patient without serious complication. The patient experienced no further episodes of bleeding during the 8 months following treatment with percutaneous injection sclerotherapy. In conclusion, percutaneous injection sclerotherapy remains an option for the treatment of patients with bleeding stomal varices.